2015
DOI: 10.18311/jnr/2015/498
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extraction Solvent on the Phytoconstituents of <i>Aegle marmelos</i> (L.) Correa

Abstract: Ipomoea reniformis Chaos is claimed in Indian traditional medical practice to be useful in the treatment of epilepsy and neurological disorders. In the present study, pretreatment effect of methanolic extract of Ipomoea reniformis on epilepsy and psychosis was evaluated in rodents using standard procedures. Besides evaluating epileptic and behavioral parameters, neurotransmitters such as Gamma-Amino Butyric Acid (GABA) in epilepsy and in psychosis dopamine, noradrenaline and serotonin contents in the rodent br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
2
1
0
1
Order By: Relevance
“…The results in this study show that, the extraction yield increases with increasing polarity of the solvent used, this may be the reason why yields of ethanol, and acetone extracts are higher than yields of water. These results are in agreement with previous studies in which, extraction yields of rice bran and some medicinal plants decreased in the following order: ethanol > acetone > distilled water [22].…”
Section: Discussionsupporting
confidence: 93%
“…The results in this study show that, the extraction yield increases with increasing polarity of the solvent used, this may be the reason why yields of ethanol, and acetone extracts are higher than yields of water. These results are in agreement with previous studies in which, extraction yields of rice bran and some medicinal plants decreased in the following order: ethanol > acetone > distilled water [22].…”
Section: Discussionsupporting
confidence: 93%
“…The extractive values of all the fractions of the rhizome did not affect the antibacterial potential of the extracts. The results of the yield of C. longa are similar to that of Sulaiman et al [36] where the effect of extraction solvent on the Phytoconstituents of Aegle marmalos showed maximum yield for hydroalcohol extract compared to other extracts. The authors also reported that yield of extract varies with extraction solvent and the part of the plant used.…”
Section: Discussionsupporting
confidence: 86%
“…It proves that ethyl acetate fraction can inhibit the performance of the pancreatic lipase enzyme as an enzyme that plays an important role in fat metabolism and fat absorption. Moreover, ethyl acetate fraction also plays a role in inhibiting α-glucosidase, thus reducing the absorption of carbohydrate [17], [18], [19].…”
Section: Discussionmentioning
confidence: 99%